Synthesis of N-Aryl and N-Heteroaryl γ-, δ-, and ε-Lactams Using Deprotometalation–Iodination and N-Arylation, and Properties Thereof - Amara, Rim; Bentabed-Ababsa, Ghenia; Hedidi, Madani; Khoury, Joseph; Awad, Haçan; Nassar, Ekhlass; Roisnel, Thierry; Dorcet, Vincent; Chevallier, Floris; Fajloun, Ziad; Mongin, Florence (Synthesis, 2017)
Xanthone, thioxanthone, fluorenone, benzophenone, 2-benzoylpyridine, dibenzofuran, and dibenzothiophene were deprotonated using a base prepared in situ from MCl2·TMEDA (M = Zn or Cd; TMEDA = N,N,N′,N′-tetramethylethylenediamine) and lithium 2,2,6,6-tetramethylpiperidide in a 1:3 ratio, as demonstrated by subsequent iodolysis. The different aryl halides were involved as partners in the N-arylation of pyrrolidin-2-one. In the presence of copper(I) iodide and tripotassium phosphate, and using dimethyl sulfoxide as solvent, the reactions could be performed in yields ranging from 40 to 70%. Most of the products were tested for their antimicrobial, antifungal, antioxidant, and cytotoxic (MCF-7) activity.
Keywords: C–N bond formation; deprotonative metalation; lactam; aromatic compound; antimicrobial activity; antifungal activity